The role of cognitive abilities in strategic innovation - أحالم إبراهيم ولي; هشيار ياسين سليمان (QALAAI ZANIST JOURNAL, 2019)
The study aims to analyze the role of knowledge capabilities in their dimensions (systematic thinking, intelligence, intuition, creativity, decision-making) in the strategic renewal of organizations. In order to achieve this, the study attempted to provide a comprehensive conceptual framework for the most important of what the authors and researchers have examined about the variables of study. The research problem was identified by posing several questions centered on the nature of the relationship and the effect between the independent variable and the dependent variable, A hypothesis was designed for the research, from which the main and subsidiary hypotheses emerged In order to verify these hypotheses, they were subjected to a set of statistical tests and a descriptive analytical approach, The sample of the research was determined from the number Head of Departments of the number of private universities in the city of Erbil.( 92) questionnaires were distributed to the responding individuals and( 86) samples were obtained, all valid for analysis, SPSS v.22 was used to study the assumed relationships in the research model, The research found a number of conclusions, the most important of which were the results of the analysis revealed the existence of positive relationships and a high level of Knowledge capabilities and strategic renewal at the macro and micro level The universities realized that their survival and sustainability in the business world depended on a combination of factors as the basis on which knowledge capabilities and strategic renewal were built. The study concluded with a number of proposals, the most important of which is the need for universities to explore new strategies to acquire skills and knowledge from external sources and transform them into new knowledge that can contribute to the renewal of their knowledge capabilities to obtain new scientific outputs.